Content Validation of checklists to assess the combination of fundamental motor skills (Research, Society and Development, 2022)
This study aimed to verify the evidences of validity of content in two checklists that analyze the combination of fundamental motor skills. To this end, the study was divided in three rounds. First, nine judges measured items of the checklists based on the Likert scale, varying from “1”, not at all to “5”, very much clear, pertinent and representative, for the content evidence validity. After the first stage of analysis, eight items were excluded in the skill to throw the ball over the shoulder (CVCt = 0.72) and in the horizontal jump (CVCt = 0.77). Then, the instruments were reduced to only four items in order to analyze the quality of the pattern of combination of fundamental motor skills. The results of the second stage of analysis presented clear, pertinent and representative to all four items of the instrument. Content validity was found for both running and throwing combination analysis instruments (CVCt = 0.89) as for running and jumping (CVCt = 0.86). However, there were still suggestions from the judges for adjustments in the wording of the items of both instruments. Therefore, after the third round of analysis, there was evidence of validity of the content to the checklists of running and throwing (CVCt = 0.89), as well as running and jumping (CVCt = 0.89). In general, the results indicated content validity evidence. The instruments can be useful tools for researchers and physical education teachers as well as sports coaches.